„Ta gorsza” – czyli o kilku wierszach Elżbiety Szemplińskiej - Wróbel, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
In the article, the author brings back the forgotten poet of the interwar period Elizabeth Szemplińska. The starting point of the discussion is the political and social situation that occurred in Poland in the thirties. The economic crisis, from which the whole of Europe was struggling from, favored radicalization among the Polish intelligence. Szemplińska openly admitted to her communist sympathies. The article remembers young poets from the Quadriga group, one of whom was also Nina Rydzewska. The group suggested the slogan „poetry socialized” showing the misery and suffering of the lowest social class. The author focused on the analysis of several lines from Szemplińska’s poems, in which the poet shows a woman of the proletariat crippled by hard work.